Perceived organizational support and entrepreneurial intention as predictors of sustainable organizational effectiveness (West African Journal on Sustainable Development, 2024)
The overall productivity and effectiveness of the workplace especially in Nigeria as a developing country, forms an unimaginable bases for sustainable development of any nation. Hence, the study examined the roles of perceived organizational support and entrepreneurial intention as predictors of sustainable organizational effectiveness in the workplace. The researcher used 180 participants drawn from private organisations in Awka, Anambra State and selected using a systematic and convenience sampling technique. The participants consisted of 78 males (43.3%) and 102 females (56.7%) with the age range of 20-60 years, mean age of 40 years and a standard deviation of 0.6. The researcher employed the use of perceived organizational support scale, entrepreneurial intention scale and organizational effectiveness scale in determining the participant’s responses.The study adopted correlational design and multiple linear regression as the study design and statistics. The first hypothesis which stated that perceived organizational support of workers will significantly predict their organizational effectiveness was accepted at B = .360, t = 24.841, p < .05. This shows that perceived organizational support significantly predicted organizational effectiveness which is needed for sustainable development. The second hypothesis which stated that entrepreneurial intention will significantly predict worker’s organizational effectiveness was accepted at B = .184, t = 2.509, p < .05. This shows that entrepreneurial intention significantly predicted organizational effectiveness for sustainable development. Furthermore, it was recommended that organizations should encourage a support system and the initiation of entrepreneurial intention among workers as it makes for the effectiveness needed for sustainable development of any organisation.
Keywords: Organisational support; Entrepreneurial intention; Organizational effectiveness